CRISPR/Cas9 establishment-mediated targeted mutagenesis in Macrobrachium nipponense - Qiao, Hui; Jiang, Sufei; Fu, Hongtuo; Xiong, Yiwei; Zhang, Wenyi; Xu, Lei; Cheng, Dan; Wang, Jisheng (Frontiers in Physiology, 2023)
Introduction: CRISPR/Cas9 is a gene-editing technology which could specifically cleave dsDNA and induce target gene mutation. CRISPR/Cas9 has been widely used in gene functional studies in many fields, such as medicine, biology, and agriculture due to its simple design, low cost, and high efficiency. Although it has been well developed in model fish and freshwater fish for gene function analysis, it is still novel in the studies dealing with economic crustacean species. Methods: In this study, we established a CRISPR/Cas9 system based on microinjection for M. nipponense, an important economic crustacean aquaculture species. The vitellogenin (Vg) gene and the eyeless (Ey) gene were selected as the targeted genes for mutation. Two sgRNAs were designed for Mn-Vg and Mn-Ey gene editing, respectively. Results and Discussion: For sg-Vg-1, the gastrula survival ratio was 8.69%, and the final hatching ratio was 4.83%. The blastula mutant ratio was 10%, and the hatching individual mutant ratio was 30%. For sg-Vg-2, the gastrula survival ratio was 5.85%, and the final hatching ratio was 3.89%. The blastula mutant ratio was 16.67%, and no mutant sequences were detected in hatching individuals. For sg-Ey-1, the gastrula survival ratio was 6.25%, and the final hatching ratio was 2.34%. The blastula mutant ratio was 10.00%, and the hatching individual mutant ratio was 66.67%. For sg-Ey-2, the gastrula survival ratio was 6.00%, and the final hatching ratio was 2.67%. No mutant sequence was detected in both blastula stage and hatching individuals. There were no significant morphological changes observed in the Mn-Vg group. Two deformed types were detected in sg-Ey-1-injected embryos. An evident developmental delay of the compound eye was detected in Ey-sg1-H1 in the zoea stage. The compound eyes of the Ey-sg1-H2 embryo could not form well-defined spheres, and the whole compound eye appeared to diffuse at the end of the late zoea stage. The establishment of a gene-editing platform based on CRISPR/Cas9 will not only provide an efficient and convenient method for gene function analysis but also provide a powerful tool for molecular-assisted breeding of Macrobrachium nipponense.